2004
DOI: 10.1097/00000542-200407000-00014
|View full text |Cite
|
Sign up to set email alerts
|

Inducible Nitric Oxide Synthase Mediates Delayed Cardioprotection Induced by Morphine In Vivo 

Abstract: : Pretreatment with morphine induces delayed cardioprotection in mice. The authors demonstrated an obligatory role for iNOS in mediating morphine-induced delayed cardioprotection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
26
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 0 publications
2
26
0
Order By: Relevance
“…PC mimetics such as NO donors (15,18), TAN-670, and CCPA have obvious clinical potential. Combined with previous studies (6,16,(25)(26)(27), the present data support the development of strategies aimed at selectively upregulating iNOS in cardiac myocytes to induce a chronic PC state.…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…PC mimetics such as NO donors (15,18), TAN-670, and CCPA have obvious clinical potential. Combined with previous studies (6,16,(25)(26)(27), the present data support the development of strategies aimed at selectively upregulating iNOS in cardiac myocytes to induce a chronic PC state.…”
Section: Discussionsupporting
confidence: 84%
“…Specifically, no data exist regarding the contributions of iNOS to the delayed infarct-sparing effects elicited by NO donors. With regard to ␦ 1 -opioid receptor-induced late PC, a recent study (16) has concluded that iNOS mediates the delayed infarctsparing actions of morphine. However, morphine is not a specific ␦ 1 -opioid receptor agonist, and, in that investigation, the duration of coronary reperfusion was limited to 2 h. It is unknown whether a 2-h reperfusion period is sufficient for accurate assessment of infarct size in mice.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These authors speculated that an increased level of endogenous opioids in bile duct-ligated rats chronically increased [Ca 2+ ]i [90]; thus, ACh could no longer increase the [Ca 2+ ]i level to stimulate cNOS to release NO. Jiang et al [91] found that infarct size in a heart subjected to coronary occlusion/reperfusion was reduced by morphine in wild-type mice, and this cardioprotective effect was abolished by S-methylthiourea sulfate and was absent in iNOS-gene-knockout mice; an increase in myocardial iNOS expression was observed after morphine administration. These authors suggested an obligatory role for iNOS in mediating morphineinduced delayed cardioprotection.…”
Section: Vascular Endothelium and Smooth Musclementioning
confidence: 99%